Southeast Asia must narrow down the yield gap to continue to be a major rice bowl - Yuan, Shen; Stuart, Alexander M.; Laborte, Alice G.; Rattalino Edreira, Juan I.; Dobermann, Achim; Kien, Le Vu Ngoc; Thúy, Lưu Thị; Paothong, Kritkamol; Traesang, Prachya; Tint, Khin Myo; San, Su Su; Villafuerte, Marcelino Q.; et al. (Springer, 2022)
Southeast Asia is a major rice-producing region with a high level of internal consumption and accounting for 40% of global rice exports. Limited land resources, climate change and yield stagnation during recent years have once again raised concerns about the capacity of the region to remain as a large net exporter. Here we use a modelling approach to map rice yield gaps and assess production potential and net exports by 2040. We find that the average yield gap represents 48% of the yield potential estimate for the region, but there are substantial differences among countries. Exploitable yield gaps are relatively large in Cambodia, Myanmar, Philippines and Thailand but comparably smaller in Indonesia and Vietnam. Continuation of current yield trends will not allow Indonesia and Philippines to meet their domestic rice demand. In contrast, closing the exploitable yield gap by half would drastically reduce the need for rice imports with an aggregated annual rice surplus of 54 million tons available for export. Our study provides insights for increasing regional production on existing cropland by narrowing existing yield gaps.